GOVERNING URBAN RESETTLEMENT: INSTITUTIONAL CHANGE AND THE POLITICS OF RELOCATION IN KOLKATA AND BEYOND - Mondal, Tamoghna (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Urban relocation and resettlement have become integral to the growth and renewal of cities worldwide, yet these processes often ignite complex governance challenges and socio-political tensions. This article adopts a globally comparative framework – with a particular focus on India’s urban context and the city of Kolkata – to examine how the relocation of communities in urban transformation projects is governed and how it connects to institutional change. Drawing on contemporary urban studies and institutional economics literature, we explore the interplay between formal policies, institutional incentives, and individual behaviors in shaping resettlement outcomes. The analysis links the micro-level decisions of households and displaced persons with the macro-level structures of governance, highlighting how individual optimizing behavior and community agency can feed back into institutional responses. Examples from Kolkata and other cities illustrate common challenges such as displacement-driven impoverishment, contested land politics, and struggles over rights, as well as innovative practices aiming for more inclusive outcomes. By situating individual and community experiences of resettlement within a broader political economy of urban transformation, the paper sheds light on how governance and institutional frameworks can either mitigate or exacerbate the hardships of relocation. The findings underscore the need for adaptive, participatory urban governance that acknowledges institutional feedback loops and prioritizes social justice in managing urban change.